The Role of Student Housing in Student Success: An Ethnographic Account (Journal of Student Affairs in Africa, 2021)
The role of university student housing in the lives of undergraduate students has changed. While student housing used to be understood only as a space to accommodate students who primarily come from out of town, now universities have started using student housing strategically to advance the success of the students. Student housing is now used to build sustainable living and learning student environments in the interests of promotion of student access and success. Through an ethnographicaccount, where the researcher spent two consecutive semesters living in an undergraduate university residence which accommodates 577 students, the article provides an 'insider-outsider' interpretation of students' context for success from one of the South African university student residences. This article uses Tinto's theory of student integration model to frame an understanding of students' experiences and perceptions of success. It further highlights socioeconomic hardships as well as stories of caring andpartnerships that students experience in their journeys towards success. These student experiences are very relevant to their integration into the university culture and systems and are critically important to the success of the student. This article concludes that the role of student housing is key to student successas it provides various opportunities for support from fellow students and staff.
Keywords: ethnography; student experiences; student housing; student success; university residence